2017
DOI: 10.1016/j.bjpt.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Functional electrical stimulation improves muscle strength and endurance in patients after cardiac surgery: a randomized controlled trial

Abstract: HighlightsFES is widely used in patients with chronic heart failure.FES increased quadriceps muscle strength after eight weeks of training.FES increased lower limb muscle endurance after eight weeks of training.FES was unable to modify functional capacity after eight weeks of training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
1
11
1
3
Order By: Relevance
“…According to our data, knee extensor muscle strength can also be used to assess the likelihood of developing complications after cardiac surgery and, in our opinion, may be preferable in this group of patients. There are studies that have shown that the electric skeletal muscle stimulation (EMS) in patients after cardiac surgery are safe [16] and can improve skeletal muscle metabolism [17]. Therefore, assessing the muscles' status before and after EMS allows to evaluate its effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…According to our data, knee extensor muscle strength can also be used to assess the likelihood of developing complications after cardiac surgery and, in our opinion, may be preferable in this group of patients. There are studies that have shown that the electric skeletal muscle stimulation (EMS) in patients after cardiac surgery are safe [16] and can improve skeletal muscle metabolism [17]. Therefore, assessing the muscles' status before and after EMS allows to evaluate its effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…It is our hope that electrical stimulation can be used as an alternate cost-effective gait rehabilitation therapy, which can help patients to increase their gait cadence while training on a treadmill. In addition to the increase in walking speed, the use of electrical stimulation has also proven to increase muscle strength and stability [29]. Together the use of entrainment by electrical stimulation may be beneficial in assisting those with movement disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used as a neuroprosthetic, which generates functional movement of paralyzed muscle such as grasping, standing, and walking [25,26]. The therapeutic application of FES has benefits of increasing muscle strength and endurance, and reducing muscle spasticity [23,[27][28][29]. Furthermore, it induces motor cortex activation through repetitive movement exercise [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%